Polański, Hitchcock i MacGuffin - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2022)
The main subject of the article is the relationship between the creative method of Roman Polanski and Alfred Hitchcock and the attitude of the Polish director to genre cinema. The author of the text, critically analyzing the earlier diagnoses of Polish monographers of Polanski’s work (Grażyna Stachówna, Mariola Dopartowa), prove that these problems are difficult to reduce to the MacGuffin issue today, because they “loop” at many levels and in various interpretative concepts, consistently eluding easy generalizations.